Sacred Simplicity? Exploring TAM and User Intent in Islamic Bank Mobile Services in Indonesia - Sultoni, Mohammad Hamim; Darmawati, Mila; Mujaddidi, Ah. Shibghatullah; Fahrurrozi, Fahrurrozi; Firmansyah, Farid (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This study explores the antecedents of customer satisfaction among mobile banking users by refining the Technology Acceptance Model (TAM) through the lens of intention to use as a mediating mechanism. In doing so, it deepens the conceptual scaffolding of TAM by juxtaposing ease, utility, and volition within a digital Islamic banking context. A survey of 150 active BSI mobile banking users across multiple provinces was analyzed using Partial-Least-Squared Structural Equation Modeling. The results indicate that ease of use significantly bolsters satisfaction—directly and indirectly—while perceived usefulness exerts its influence chiefly through intention. Surprisingly, usefulness alone fails to predict satisfaction, suggesting a more nuanced psychological calculus in fintech adoption. These insights furnish digital banking strategists with a practical blueprint: prioritize interface simplicity to cultivate loyalty and perceived value.